Teaching English Using Poetry: An Alternative to Implement Contextual Teaching and Learning - Samanik, Samanik (University of Muhammadiyah Prof. DR. HAMKA, 2018)
This paper describes poetry as an alternative to implement Contextual Teaching and Learning (CTL). CTL places learning and learning activities in a real-life context, incorporating not only what is learned but also why students should learn it. Meanwhile, poetry is chosen for its authenticity, in which, all nations have their own record on poetry. The classroom activities which involve poetry are poetry production (writing), poetry performance (reading), and poetry appreciation (speaking). By using poetry, learning processes are expected to meet the seven main components of effective learning: constructivism, questioning, inquiry, learning community, modeling, and authentic assessment. Moreover, the learning process can develop not only language skills but also critical thinking skill.  Keywords: Contextual Teaching and Learning (CTL), poetry, components of ideal teaching and learning